Information systems concepts for management - Lucas, Henry C. (New York : McGraw-Hill, 1982)
Presents coverage of technical and managerial concepts relating to the use of computers in business. The text focuses on material that managers need to know and reflects trends in global economy, distributed systems, end-use computing, group decision support systems, multimedia and executive IT.
Includes index
Includes bibliographical references: p. 503-507.
ijb 16/01/2019
Loans
Keywords: Management information systems; Information systems